HARMONY AND MODERNITY: REINVENTION OF LIMPAPEH MOTIF AT RUMAH GADANG IN CONTEMPORARY TEXTILE DESIGN - Miswar , Vanesha; Minawati , Rosta; Mulyadi; Miswar (PT. Antis International Publisher, 2024)
Objective: This study explores the reinvention of the Limpapeh House Tower motif in contemporary textile design, focusing on the integration of traditional Minangkabau elements with modern symbolism that reflects current social dynamics. Method: The design process involves a comprehensive understanding of the philosophical meaning of the Limpapeh motif, followed by the introduction of abstract patterns representing the disruption of traditional values in the face of modern challenges. The study also examines the use of contrasting colors and asymmetrical compositions to visually symbolize the tension between tradition and modernity. Results: The reinvention of the Limpapeh motif into a contemporary textile design produces works that are not only visually striking but also culturally significant. The contrast between the traditional symbolism of balance and stability and the abstract elements reflecting social disruption highlights the evolving cultural and social landscape of Minangkabau society. This process creates a space for reflection on the preservation of cultural values amid modern change. Novelty: This research contributes to the preservation of Minangkabau culture by presenting the Limpapeh motif in a dynamic, modern form. It also serves as a tribute to the symbolic power of the Limpapeh as a cultural pillar, while opening new avenues for interpretation and exploration in contemporary design.